The Meaning of Local Wisdom in Do-Mooru (Weaving) Tradition in the Muna Tribe at Muna Regency, The Province of Southeast Sulawesi, Indonesia - Bahtiar; Musafar; Sifatu, Wa Ode; Basri, La Ode Ali; Suardika, I. Ketut; Ana, Haerun; Jamiludin; Aso, La (Advances in Social Sciences Research Journal, 2022)
The objective of this study was to analyze the meaning of local wisdom of do-mooru (weaving) tradition in the Muna tribe at Muna Regency, the Province of Southeast Sulawesi, Indonesia. This research was conducted at Masalili Village, Kontunaga Sub-District, Muna Regency of Southeast Sulawesi Province, Indonesia. This research is qualitative by using three data sources, namely primary data, secondary data, and tertiary data. The data were collected through participant observation, in-depth interviews, and focused discussions. The data analysis technique was carried out through categorization, classification, and reduction, then processed by reception, comparison, and description techniques. The results of this study showed that the meaning of local wisdom in do-mooru (weaving) tradition in the Muna tribe consists of (1) identity meaning, (2) social solidarity meaning, (3) politeness meaning, and (4) inheritance meaning. The meaning of identity is represented by kamooru weaved cloth which contains symbols of the wearer’s social identity and contains noble values ​​which are one of the identities of the people in Muna Regency. The meaning of social solidarity can be seen in the attitude of the weaving craftsmen who have each other and try to correct the shortcomings in each do-mooru (weaving) process. The meaning of politeness can be seen in the use of kamooru motif according to the social status of the wearer, which is one way to provide education to the community in obeying social norms that should be obeyed. Meanwhile, the meaning of inheritance can be seen from the efforts to continue to maintain the continuity of do-mooru tradition from generation to generation.